2023
DOI: 10.1038/s41420-023-01441-x
|View full text |Cite
|
Sign up to set email alerts
|

Senataxin and R-loops homeostasis: multifaced implications in carcinogenesis

Abstract: R-loops are inherent byproducts of transcription consisting of an RNA:DNA hybrid and a displaced single-stranded DNA. These structures are of key importance in controlling numerous physiological processes and their homeostasis is tightly controlled by the activities of several enzymes deputed to process R-loops and prevent their unproper accumulation. Senataxin (SETX) is an RNA/DNA helicase which catalyzes the unwinding of RNA:DNA hybrid portion of the R-loops, promoting thus their resolution. The key importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 119 publications
1
1
0
Order By: Relevance
“…Although their roles in LN remain incompletely elucidated, we observed that decreased expression of PRODH and TXN2 may contribute to the pathogenesis of LN, suggesting potential therapeutic targets for LN by enhancing the PPAR signalling pathway. Similarly, our study detected SETX, an RNA/DNA helicase crucial for transcription termination and genomic integrity, 55 whose expression levels were significantly upregulated in patients with LN. We speculated that SETX may lead to abnormalities in DNA damage repair and transcriptional regulation, contributing to the pathogenesis of LN.…”
Section: Lupussupporting
confidence: 66%
“…Although their roles in LN remain incompletely elucidated, we observed that decreased expression of PRODH and TXN2 may contribute to the pathogenesis of LN, suggesting potential therapeutic targets for LN by enhancing the PPAR signalling pathway. Similarly, our study detected SETX, an RNA/DNA helicase crucial for transcription termination and genomic integrity, 55 whose expression levels were significantly upregulated in patients with LN. We speculated that SETX may lead to abnormalities in DNA damage repair and transcriptional regulation, contributing to the pathogenesis of LN.…”
Section: Lupussupporting
confidence: 66%
“…Using the energy from ATP hydrolysis, they can unwind the hydrogen-bonded base pairs, creating DNA regions that are accessible to cellular machinery like DNA polymerases or RNA polymerases [105,106]. RNA-DNA helicases, such as Aquarius (AQR) and SETX, are responsible for unwinding and dissociating the RNA-DNA hybrid structure, actively promoting the resolution of R-loops to maintain genomic integrity and facilitating various cellular processes [107][108][109].…”
Section: Rna-dna Helicasesmentioning
confidence: 99%